Revolutionizing Rural Marketing in India: A Study of Social Media and CRM Strategies in Selling Consumer Products - Gattani, Prafull (Digital Repository of Theses - SSBM Geneva, 2025)
As the impact of digital technologies has grown, rural markets have experienced profound changes in the past several years. Traditional methods of reaching customers in rural areas have given way to new channels made possible by the proliferation of cellphones and the Internet. As a result of this change, social media platforms are becoming potent instruments for reaching customers, swaying their opinions, and raising brand recognition. Customers in rural areas, who were previously ignored by big brands, are now the focus of personalized digital marketing campaigns.